Enhancing Multimodal Text : Digital Flashcard for English Writting Skill Development - Novita, Anggun Triya; saifulloh, Ahmad Iklil; Lindawati, Rini (PT. Kreasi Karya Majakata, 2024)
This study investigates the effectiveness of multimodal text methods to enhance narrative writing skills of EFL students at SMP Terpadu Darul Dakwah. The research employs a pre-experimental design involving pre-tests, treatments, and post-tests to measure the impact of teaching narrative texts using folktales packaged in flashcards. The results indicate a significant improvement in students' writing abilities, through the increased average scores from pre-test to post-test. The study also incorporates responsive teaching with barcode flashcards to integrate technology into the learning process, making it more engaging and relevant for students. Multimodal texts, combining video, audio, and visual elements, can effectively enhance language skills and student engagement in writing narrative texts. The research provides valuable insights for educators seeking innovative methods to improve writing instruction and suggests that incorporating multimodal texts and folktales can significantly enhance EFL students' narrative writing skills.